The Development of an Instrument for Assessing Pre-Service Teachers' and Graduates' Perceptions of the Physics Education Curriculum (PPEC) - Maison; Treagust, David (SEAMEO RECSAM, 2011)
This study describes the development of an instrument to evaluate pre-service teachers’ and graduates’ perceptions of the physics education curriculum in Indonesian higher education institutions in four categories namely, (1) approaches to teaching physics (AT), (2) the aims and objectives of the physics education curriculum (AO),(3) interest in physics (IP), and (4) approaches to learning physics (AL). The Perceptions of the Physics Education Curriculum (PPEC) questionnaire, consisting of 47 items, was administered to 287 pre-service teachers and graduates from two universities, who varied in grades, sex, and achievement level. Based on item-scale correlations and factor analysis, nine items were removed. The rotated factor matrix, using varimax rotation, supported the four-scale structure of the final version of the 38-item PPEC questionnaire. The four categories had high Cronbach’s alpha values ranging from 0.75-0.84. These results confirmed that the instrument has satisfactory reliability, statistical validity and a good factor structure.